Sustainability of natural tourism attraction and satisfaction - Y. Yuliana; A.M. Ningsih; V. Kristiana; A.P. Maharani; C. Syahni (Global Journal of Environmental Science and Management, 2025)
BACKGROUND AND OBJECTIVES: Batu Katak is a small dream village located on the edge of Gunung Leuser National Park in North Sumatra, Indonesia. Nature tourism is full of natural charm. It is one of the destinations to get away from the crowds and spend a holiday to communicate with nature. On one side of the village, there is a very diverse and interesting karst forest, full of cave systems and interesting landscapes, and across the river is the famous National Park. The attraction of Batu Katak nature tourism is trekking, and the uniqueness of the flora and fauna offered, including the giant Rafflesia flower and Amorphophallus found in the area. This study aims to examine the effect of tourist attraction and tourist satisfaction on the revisit intention of tourists in the case of Batu Katak Natural Tourism in Indonesia.METHODS: Tourists who had visited Batu Katak Nature Tourism comprised the study''s population. In this investigation, the sample size was 350 people who had just visited the Batu Katak Park nature tourism. Structural equation modeling, a multivariate analysis tool applied in this work, describes the simultaneous linear relationship between elements directly unobserved (latent variables) and observation variables (indicators). A component-based model of structural equations method called partial least squares is implemented.FINDINGS: This investigation discovered that tourist attraction affects the revisit intention positively and significantly. The tourist attraction effect was positive and significant on satisfaction. Tourist satisfaction effect revisit Intention positively and significantly. This analysis also examines the indirect effects of a tourist attraction on revisit intention by tourist satisfaction as mediation. The result found that tourist satisfaction mediates the impact of tourist attraction on revisit intention.CONCLUSION: Tourist attractions have made strong effect on tourist satisfaction. Tourist satisfaction has a significant contribution to revisit intention, and tourist attractions have a strong effect on tourist revisit intention. This study shows that tourist attractions are the most important phase in determining a tourist destination. Tourist attractions after visiting a natural tourist area will affect their desire and decision to revisit, and this requires the management''s capacity to sustain and improve tourist sites according to tourist needs, desires, satisfaction, and perceptions.  The findings also found that tourist attractions affect revisit intention through the satisfaction of tourists.  Tourist satisfaction plays an important and strong role in making tourists want to visit again. Satisfied tourists strengthen the tourist attractions’ effect on return visits.